2019
DOI: 10.1038/s41467-019-12052-5
|View full text |Cite
|
Sign up to set email alerts
|

Soybean antiviral immunity conferred by dsRNase targets the viral replication complex

Abstract: Eukaryotic positive-strand RNA viruses replicate their genomes in membranous compartments formed in a host cell, which sequesters the dsRNA replication intermediate from antiviral immune surveillance. Here, we find that soybean has developed a way to overcome this sequestration. We report the positional cloning of the broad-spectrum soybean mosaic virus resistance gene Rsv4, which encodes an RNase H family protein with dsRNA-degrading activity. An active-site mutant of Rsv4 is incapable of inhibiting virus mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 65 publications
1
41
1
Order By: Relevance
“…Another type of R-gene was identified in soybean and confers broad-spectrum resistance to potyviruses. The Rsv4 gene encodes an RNase H protein that is able to interact with viral RNA polymerase complex and, thus, most probably degrades viral RNA when in dsRNA form [49].…”
Section: Molecular Mechanisms Underlying Resistance To Pvymentioning
confidence: 99%
“…Another type of R-gene was identified in soybean and confers broad-spectrum resistance to potyviruses. The Rsv4 gene encodes an RNase H protein that is able to interact with viral RNA polymerase complex and, thus, most probably degrades viral RNA when in dsRNA form [49].…”
Section: Molecular Mechanisms Underlying Resistance To Pvymentioning
confidence: 99%
“…Resistance provided by Rsv4 is unique in that it is not conferred via an NLR-type protein, as Rsv4 encodes an RNAse-H family protein with the ability to degrade dsRNA. Interactions between the SMV P3 protein and Rsv4 promote dsRNA degradation and prevent viral replication (Hayes et al, 2000;Maroof et al, 2010;Ishibashi et al, 2019). The ability of Rsv4 to prevent infection declines with age, as mature plants are more susceptible to infection (Hayes et al, 2000;Maroof et al, 2010).…”
Section: Extreme Resistance To Viruses In Soybeanmentioning
confidence: 99%
“…A recent study showed that Rsv4 encodes an RNase-H family protein with dsRNA-degrading activity and interacts with the P3 protein of SMV to promote the fusion of dsRNAses with host factors involved in virus replication. This fusion result in the degradation of the viral dsRNAs [65].…”
Section: Rsv Genesmentioning
confidence: 99%
“…The catalytic subunit of RdRp [65][66][67] CP A 'bridge' between virion particles and aphid stylets in aphid transmission [47], cell-to-cell movement, virus assembly [68,69]…”
Section: Introductionmentioning
confidence: 99%